PENGARUH SELF-DISCLOSURE KEPADA CHATBOT AI DENGAN PSYCHOLOGICAL WELL-BEING PADA GENERASI Z: PERAN MEDIASI PERCEIVED EMPATHY - Silvina Sari, Anisa; Mardianto; Akbar, Amin; Rizal Kurniawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Technological advancements have given rise to a generation that is increasingly connected to artificial intelligence (AI). AI chatbots are used not only to obtain information but also as a medium for self-disclosure to gain emotional relief and support related to psychological well-being. However, the effect of self-disclosure to AI chatbots on psychological well-being still requires further clarification, particularly when considering the mediating role of perceived empathy. The purpose of this study is to examine the effect of self-disclosure to AI chatbots on psychological well-being among Generation Z and to test the mediating role of perceived empathy. This study employs a quantitative approach using an explanatory research design involving 437 AI users. Data were collected using Ryff’s Psychological Well-Being Scale (RPWB), the Wheeless Self-Disclosure Scale (WSDS), and the Perceived Empathy Trust Scale (PETS), and were analyzed using simple linear regression and PROCESS Model 4. The results indicate that self-disclosure to an AI chatbot does not significantly affect psychological well-being (p > 0.05). However, perceived empathy mediated the effect of self-disclosure on psychological well-being (BootLLCI = 0.006; BootULCI = 0.051). These findings suggest that perceived empathy is an important mechanism that explains the influence of self-disclosure to AI chatbots on psychological well-being. This study has implications for AI chatbot developers to consider designing chatbots that can respond more empathetically and relevantly to support users’ psychological well-being.